Turn-key mapping of cell receptor force orientation and magnitude using a commercial structured illumination microscope - Aaron Blanchard (Nature Portfolio, 2021)
The authors have recently developed molecular force microscopy (MFM) which uses fluorescence polarisation to measure cell-surface receptor force orientation. Here they show that structured illumination microscopes, which inherently use fluorescence polarisation, can be used for MFM in a turn-key manner.